Comparison between alcohol‐ and hepatitis C virus‐related hepatocellular carcinoma: clinical presentation, treatment and outcome. Issue 3 (14th December 2015) - Bucci, L.; Garuti, F.; Camelli, V.; Lenzi, B.; Farinati, F.; Giannini, E. G.; Ciccarese, F.; Piscaglia, F.; Rapaccini, G. L.; Di Marco, M.; Caturelli, E.; Zoli, M.; et al.
Summary: Background: Hepatitis C virus (HCV) and alcohol abuse are the main risk factors for hepatocellular carcinoma (HCC) in Western countries. Aim: To investigate the role of alcoholic aetiology on clinical presentation, treatment and outcome of HCC as well as on each Barcelona Clinic Liver Cancer (BCLC) stage, as compared to HCV‐related HCCs. Methods: A total of 1642 HCV and 573 alcoholic patients from the Italian Liver Cancer (ITA.LI.CA) database, diagnosed with HCC between January 2000 and December 2012 were compared for age, gender, type of diagnosis, tumour burden, portal vein thrombosis (PVT), oesophageal varices, liver function tests, alpha‐fetoprotein, BCLC, treatment and survival. Aetiology was tested as predictor of survival in multivariate Cox regression models and according to HCC stages. Results: Cirrhosis was present in 96% of cases in both groups. Alcoholic patients were younger, more likely male, with HCC diagnosed outside surveillance, in intermediate/terminal BCLC stage and had worse liver function. After adjustment for the lead‐time, median (95% CI) overall survival (OS) was 27.4 months (21.5–33.2) in alcoholic and 33.6 months (30.7–36.5) in HCV patients ( P = 0.021). The prognostic role of aetiology disappeared when survival was assessed in each BCLC stage and in the Cox regression multivariate models. Conclusions: Alcoholic aetiology affects survival of HCC patients through its negative effects on secondary prevention and cancer presentation but not through a greater cancer aggressiveness or worse treatment result. In fact, survival adjusted for confounding factors was similar in alcoholic and HCV patients.